Update on Foregut Molecular Embryology and Role of Regenerative Medicine Therapies - Perin, Silvia; McCann, Conor J.; Borrelli, Osvaldo; De Coppi, Paolo; Thapar, Nikhil (Frontiers in Pediatrics, 2017)
Oesophageal Atresia (OA) represents one of the commonest and most severe developmental disorders of the foregut, the most proximal segment of the gastrointestinal tract (oesophagus and stomach) in embryological terms. Of intrigue is the common origin from this foregut of two very diverse functional entities, the digestive and respiratory systems. OA appears to result from incomplete separation of the ventral and dorsal parts of the foregut during development, resulting in disruption of oesophageal anatomy and frequent association with tracheo-oesophageal fistula (TOF). Not surprisingly, and likely inherent to OA, are associated abnormalities in components of the enteric neuro-musculature and ultimately loss of oesophageal functional integrity. An appreciation of such developmental processes and associated defects has not only enhanced our understanding of the aetiopathogenesis underlying such devastating defects, but also highlighted the potential of novel corrective therapies. There has been considerable progress in the identification and propagation of neural crest stem cells from the gastrointestinal tract itself or derived from pluripotent cells. Such cells have been successfully transplanted into models of enteric neuropathy confirming their ability to functionally integrate and replenish missing or defective enteric nerves. Combinatorial approaches in tissue engineering hold significant promise for the generation of organ specific scaffolds such as the oesophagus with current initiatives directed towards their cellularisation to facilitate optimal function. This chapter outlines the most current understanding of the molecular embryology underlying foregut development and OA, and also explores the promise of regenerative medicine.